2006
DOI: 10.2334/josnusd.48.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of image performance between cone-beam computed tomography for dental use and four-row multidetector helical CT

Abstract: The authors evaluated the imaging performance of cone-beam computed tomography (CBCT) for dental use using 3DX multi-image micro-CT (Morita Co., Kyoto, Japan) and four-row multi-detector helical computed tomography (MDCT) using an Asteion (Toshiba, Tokyo, Japan). A dried right maxillary bone was cut into eight slices 2 mm thick toward the zygomatico-palate and used as a phantom. Images of the phantom were then taken using 3DX and MDCT. The images of two bone slices were evaluated by five dentists for image qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 16 publications
0
55
2
8
Order By: Relevance
“…Maximum resolution (150 nm) was obtained by adding more improvements to the detector and the sample stage. The resolution obtained in our study (150 nm) is greater than the higher resolution (200 nm) reported by other studies 10,11) . Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Maximum resolution (150 nm) was obtained by adding more improvements to the detector and the sample stage. The resolution obtained in our study (150 nm) is greater than the higher resolution (200 nm) reported by other studies 10,11) . Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…These changes allow a less expensive, smaller machine that exposes the patient to approximately 20% of the radiation of an helical CT, equivalent to the exposure from a full-mouth periapical series. Due to a difference in voxel size, CBCT of a limited area is also very effective in achieving high spatial resolution in comparison with conventional CT (9). Clinically, CBCT has a wide range of applications; for example, it may be used to determine the extent and condition of the internal structure of lesions, the fracture of teeth roots, the condition of impacted teeth and pathologic conditions in jaw bones (8).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 These advantages make CBCT technology particularly well suited to hard tissue imaging and dentistry. As the X-ray dose is so much lower than for conventional CT scanners, it is diffi cult to justify the use of conventional CT for elective dental and maxillofacial procedures when CBCT is available.…”
Section: Field Of Viewmentioning
confidence: 99%